2018
DOI: 10.1016/j.ssmph.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Social network correlates of IPV acceptance in rural Honduras and rural Uganda

Abstract: We investigated the household-level social network correlates of acceptance of intimate partner violence (IPV) in rural, agrarian settings of Honduras and Uganda, two low-income countries with unequal access to resources based upon gender. We collected complete social network data in each location (Honduras in 2014 and Uganda in 2012), across a diverse range of relationships, and then created a measure of household cohesion by calculating the degree to which members of a household nominated each other as impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Although the prevalence of physical violence acceptance was lower than the other two dimensions, nearly half of the sample accepted at least one situation where physical threat was present. This scenario suggests that, despite its rejection, physical violence is still considered bearable and culturally accepted, which agrees with previous reports describing physical aggression between inti-mate partners as part of romantic relationships (Machado et al, 2014), deserved for disobeying the partner (Molina & Moreno, 2015), justified when wives do not make what it is expected of them (Shakya et al, 2018), and a way to solve conflicts (Guzmán González et al, 2016). Thus, it is possible that the high acceptance of abuse, controlling interactions between partners and physical violence found in this study, reflects a bigger picture about rule enactment between romantic partners.…”
Section: Discussionsupporting
confidence: 87%
“…Although the prevalence of physical violence acceptance was lower than the other two dimensions, nearly half of the sample accepted at least one situation where physical threat was present. This scenario suggests that, despite its rejection, physical violence is still considered bearable and culturally accepted, which agrees with previous reports describing physical aggression between inti-mate partners as part of romantic relationships (Machado et al, 2014), deserved for disobeying the partner (Molina & Moreno, 2015), justified when wives do not make what it is expected of them (Shakya et al, 2018), and a way to solve conflicts (Guzmán González et al, 2016). Thus, it is possible that the high acceptance of abuse, controlling interactions between partners and physical violence found in this study, reflects a bigger picture about rule enactment between romantic partners.…”
Section: Discussionsupporting
confidence: 87%
“…Among studies of attitudes towards IPV, four studies found evidence that individual attitudes towards IPV were strongly influenced by IPV acceptance among household members (Shakya et al, 2016(Shakya et al, , 2018, broader social network members (Sandberg et al, 2021), and peers (Swartout, 2013). However, other studies found only weak or no social network influences on attitudes towards sexual violence among adolescents and when accounting for individual perceptions of network members' attitudes (Itaru, 2003).…”
Section: Social Network Analysis Studies (N = 45)mentioning
confidence: 99%
“…While many studies aggregate individual-level beliefs as a proxy for social norms, aggregated individual beliefs fail to capture key components of social norms: social expectations of others in the community, reference groups, and social sanctions and approval [ 26 ]. Few studies have examined injunctive norms or second order beliefs specific to IPV, but those that do suggest that perceived social norms and peer behaviour are related to individual IPV behaviour and that IPV can potentially be prevented by changing the social context [ 35 , 43 , 44 , 51 ]. Violence prevention researchers are clear that effective interventions need to target social and contextual factors, like social norms, yet these efforts are substantially limited by lack of effective social norms measurement tools [ 5 , 16 , 24 ].…”
Section: Introductionmentioning
confidence: 99%